The Role of Schools and Physical Education in Supporting Sports Achievement: Literature Review - Dahlan, Firmansyah; Mahyuddin, Reza; Muslim, Muslim (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
The Great Design of National Sports (DBON) of the Republic of Indonesia has been ratified, invited, and socialized. The urgency in succeeding the Law is the synergy of all parties. The question that arises is, “how is this synergy built?”. For this reason, this literature review is directed to describe the synergies (positions, roles, and benefits) of schools (extracurricular sports and Physical Education) related to achievement sports that are disseminated in scientific journals. Databases used are; Sinta, google scholar, sciencedirect.com, springer, the Mendeley application, VOSviewer, and Publish or Perish. Results; 1) Schools are strategic places to promote achievement sports. 2) Physical education plays an important role in the mass and nursery stages. 3) Achievement sports have many benefits for children, but with a clear reference that is not for all children. 4) Important factors for the development of achievement sports in schools are an appropriate curriculum, run by professionals, adequate networks, parents, and government commitment. 5) Associations/ federations and sports clubs provide experts and staff, the government provides sports facilities, and Physical Education teachers and students become the subject of the development. 6) Sport and physical education extracurricular activities have a positive influence on children’s academic abilities (indirectly) because children are happy and feel at home in school, which increases their self-confidence and self-esteem. 7) Extracurricular sports do not interfere with children’s academic achievements when carried out properly.